Design Of Mobile Shopping Cart Robot Based On IoT(Internet Of Thing) - Hanafi Ramadhana; Solly Aryza; Siti Anisah (INFOKUM, 2021)
Many people are shopping in supermarkets so that baskets and trolleys are usually provided to carry groceries, resulting in frequent cases such as missing or confused baskets. As a result of these problems, a new method is needed in dealing with the problem of swapping shopping cart trolleys. This study describes information about automatic customer follower trolley robots based on image processing and microcontrollers. The design of this control system uses an Arduino Pro Mini Microcontroller which is connected to GPS, Ultrasonic sensors, ESP 8266, and DC motors. Ultrasonic Sensors, The author's purpose is to make research on this trolley robot to make it easier and more comfortable for supermarket customers to shop and carry their groceries, where the trolley is made to be able to follow the user's movements without the need to push it so that customers just have to choose the items they buy and customers can walk in front of their shopping trolleys. The additional devices needed to move the trolley automatically include cameras, microcontrollers, DC motors, servo motors, motor drivers, and batteries mounted on the trolley. Image processing uses a camera on a system that is made to work by detecting the color of the object that has been determined to determine the distance of the object from the trolley. The method used to process image processing is a hue-based color filtering algorithm. So that in its use the trolley is able to move automatically following the customer. The final result of this automatic follower trolley design is a success rate of 80% with the maximum distance between the object and the trolley is 5.65m.